Academic and cognitive-affective factors as predictors of the intention to graduate with a thesis in Psychology students - Capa-Luque, Walter (2022)
A predictive model of the intention to graduate with a thesis, based on academic and cognitive-affective factors, is examined in a sample of 198 students from the first to the fifth year of psychology. The structural model tested by Path Analysis presented an adequate adjustment (CFI >.95 and RMSEA <.08), observing that engagement and attitude towards statistics indirectly regulate the intentionality of a thesis, while self-efficacy and methodological competencies have direct effects on intentionality. When there are adequate methodological competencies, the prognosis for doing a thesis is 82.6%, while a favorable attitude towards statistics forecasts 80.6% of the interest of graduating with a thesis.